Multifunctional Flavonoid‐Silica Nanohydrogel Enables Simultaneous Inhibition of Tumor Recurrence and Bacterial Infection in Post‐Surgical Treatment. Issue 5 (26th November 2021) - Chu, Binbin; Wu, Sicong; Yang, Yunmin; Song, Bin; Wang, Houyu; He, Yao
Abstract: A strategy to synthesize water‐soluble and fluorescent flavonoid‐silica nanocomposites (FSiNCs) simultaneously featuring anti‐tumor and anti‐bacterial abilities is developed. Furthermore, it is demonstrated that the therapeutic effects of FSiNCs are associated with the selective accumulation of reactive oxide species in both tumor and bacteria cells. Following that, the resultant FSiNCs are incorporated with thrombin and fibrinogen, being sprayed onto the tumor surgical wound site to in situ form fibrin gel (FSiNCs@Fibrin). Remarkably, such FSiNCs@Fibrin results in an ≈18‐fold reduction in intratumoral bacteria numbers and ≈12‐fold decrease in tumor regrowth compared to equivalent free flavonoid‐loaded gel. Abstract : In this work, a facile microwave‐assisted synthetic strategy to prepare high‐performance water‐soluble and fluorescent flavonoids‐silica nanocomposites (namely FSiNCs) simultaneously featuring anti‐tumor and anti‐bacterial abilities is developed, which can be sprayed onto the tumor surgical wound site to in situ form fibrin gel (FSiNCs@Fibrin), allowing high‐efficacy inhibition of tumor recurrence and bacterial infection.